Characterization of the Citrobacter rodentium Cpx regulon and its role in host infection. Issue 3 (11th February 2019) - Vogt, Stefanie L.; Scholz, Roland; Peng, Yun; Guest, Randi L.; Scott, Nichollas E.; Woodward, Sarah E.; Foster, Leonard J.; Raivio, Tracy L.; Finlay, B. Brett
Summary: Envelope‐localized proteins, such as adhesins and secretion systems, play critical roles in host infection by Gram‐negative pathogens. As such, their folding is monitored by envelope stress response systems. Previous studies demonstrated that the Cpx envelope stress response is required for virulence of Citrobacter rodentium, a murine pathogen used to model infections by the human pathogens enteropathogenic and enterohemorrhagic Escherichia coli ; however, the mechanisms by which the Cpx response promotes host infection were previously unknown. Here, we characterized the C. rodentium Cpx regulon in order to identify genes required for host infection. Using transcriptomic and proteomic approaches, we found that the Cpx response upregulates envelope‐localized protein folding and degrading factors but downregulates pilus genes and type III secretion effectors. Mouse infections with C. rodentium strains lacking individual Cpx‐regulated genes showed that the chaperone/protease DegP and the disulfide bond oxidoreductase DsbA were essential for infection, but Cpx regulation of these genes did not fully account for attenuation of C. rodentium ΔcpxRA . Both deletion of dsbA and treatment with the reducing agent dithiothreitol activated the C. rodentium Cpx response, suggesting that it may sense disruption of disulfide bonding. Our results highlight the importance of envelope protein folding in host infection by Gram‐negative pathogens. Abstract : The Cpx envelope stress response senses envelope protein misfolding and is required for virulence of many pathogens, including the murine gastrointestinal pathogen Citrobacter rodentium . Here, we show that the C. rodentium Cpx response promotes expression of numerous envelope‐localized proteases and chaperones – including DegP and DsbA, which are required for host infection – while inhibiting expression of the Kfc pilus and several type III secreted effectors.